COUNTRY FOCUS Development of SMEs in India - Sampa Banerjee (International Journal of Small and Medium Enterprises and Business Sustainability, 2016)
Micro, small and medium enterprises (MSMEs) are at the centre stage of socio –economic development of emerging economies across the world and India is no exception. Rather it is MSME sector that is enabling the country to emerge as one of the leading economies in the world.Indian MSME Sector has approximately 45 million units that produce more than 6,000 products ranging from traditional to high-tech items including 67 per cent from manufacturing goods, 17 per cent from services and 16 per cent from repairs and maintenance. The sector is driving sustainable growth in Indian economy by providing employment to around 101 million people, accounts for 45 per cent of the manufacturing output, 40 per cent of the country's exports and contributes between 8 per cent and 9 per cent to the country's gross domestic product (GDP). MSME in India has the potential to increase the share of contribution to GDP from the current 8 per cent to about 15 per cent by the year 2020.Not only large industries, ancillary units and microenterprises are also contributing enormously to the socio-economic development of the country including Khadi and Village Industries (KVI) and Coir Industry or agro-based traditional industries.Khadi and Village Industries (KVI) are considered to be national heritages of India that is creating employment opportunities to large segment of rural people at a very low per capita investment while fulfilling the basic needs of processed goods of the vast rural sector of the country.Coir Industry or agro-based industry on the other hand is potentially creating economic development in the state of Kerala, Tamil Nadu, Karnataka, Andhra Pradesh, Odisha, West Bengal, Maharashtra, Assam, Tripura, etc and are driving export, technological interventions and diversified products to not only India but also globally.MSME sector in India is governed by Micro, Small and Medium Enterprises Development (MSMED) Act that was declared in 2006 by Ministry of MSME, government of India. The Act defines the MSMEs into three categories of micro, small and medium enterprises based on the number of employees and capital investment, facilitate the development of MSMEs in India, address their policy issues and enhance their competitiveness.The ministry along with states promotes entrepreneurship, employment and livelihood opportunities and enhance the competitiveness of MSMEs through various schemes/programmes, provide adequate flow of credit, support technology up gradation, provide infrastructural facilities, facilitate quality certifications, provide training for skill development, support innovation, support labor welfare, provide asses to domestic and export markets , cluster development etc.